PERANCANGAN MEDIA PEMBELAJARAN MATEMATIKA MATERI STATISTIKA BERBASIS FLASH UNTUK SISWA KELAS 6 SD ISLAM TERPADU CAHAYA UMMAT KARANGJATI - Daniel Rudjiono; Setyo Adi Nugroho; Kharolina Arifianti (STEKOM PRESS, 2021)
Mathematics is an applicable science and very close to human life, so mathematics is very important to learn from elementary school. However, the mathematics competence of elementary school students in Indonesia is relatively low. One of them is SD IT Cahaya Ummat which is located in Karangjati, Kecamatan Bergas, Kabupaten Semarang, the grade 6 students' average mathematics score is lower than other subjects. So far, learning is still conventional in nature with learning resources in the form of printed books, thus it is necessary to have learning innovations to increase students' interest in learning mathematics.The design of interactive media as a learning aid can be a solution to attract students' attention to be more focused when the teacher explains math material in class. When students feel interested and focused on learning, learning will be more effective so that students' understanding of the material presented by the teacher will also increase.Interactive learning media made with Adobe Flash CS5.5 to combine text, images, sound, and animation will make the application more attractive, so that students are more interested in learning mathematics with statistics material. The results of the validation score obtained from media experts are 34, material experts 39, and users 35, so this learning media product is classified as a very good category, so it is valid to be used.